Efektifitas Penurunan Kadar Pb (Timbal ) Limbah Cair Rumah Sakit Mengunakan Koagulan Alami - Awaliah Rahmat (Lembaga Pengembangan Kinerja Dosen, 2025)
The presence of heavy metals in waste is one of the variables that can pollute and damage the environment. Lead is one of the chemical contents that can be found in hospital liquid waste. Hospital liquid waste comes from work unit processes throughout the hospital environment which contains dangerous chemicals so it needs to be processed before being discharged into the environment. Research has been carried out using the coagulation-flocculation method using sugar palm seeds as a biocoagulant. The aim of this research is to find out how the palm seed coagulant mass influences in reducing lead (Pb) levels. hospital wastewater with the addition of variations in coagulant mass, namely 0.3%, 0.4%, 0.5%, 0.6% and 0.7%. From the filtrate resulting from coagulation-flocculation which was then analyzed based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.68 of 2016 concerning Domestic Wastewater Quality Standards, from the results of this research it is known that sugar palm seeds as a biocoagulant are able to reduce the most optimal PB concentration when the coagulant concentration is added to 0.6%.